Cadmium-stress mitigation through gene expression of rice and silicon addition - Lin, Hongmei; Fang, Changxun; Li, Yingzhe; Lin, Weiwei; He, Jianyu; Lin, Ruiyu; Lin, Wenxiong (Plant growth regulation, 2017)
Cadmium (Cd) pollution is one of the major concerns in the development of sustainable agriculture, particularly for rice production. Silicon (Si) was recently recognized for its ability to mitigate a variety of abiotic stresses including that caused by Cd on rice. However, mechanism of the complex process is still not fully understood. Under Cd-stress, the low Si-influx 1-RNAi transgenic Lemont rice ( Lsi1 -RNAi line) exhibited an increased Cd-uptake over its counterparts, the wild type and the Lsi1 -overexpression transgenic rice ( Lsi1 -OE line). In contrast, the Lsi1 expression-enhanced Lsi1 -OE line showed the greatest Si-uptake among the three lines, with the highest activities on anti-oxidants (such as, superoxide dismutase) and the lowest content of malondialdehyde. Lsi1 also displayed a negative regulation on Low Cd gene and the natural resistance-associated macrophage proteins, Nramp5 , indicating its capacity to alleviate Cd-stress on rice. The results obtained by this study suggested that the mitigation of Cd-toxicity on rice by Si might involve functions, such as the inhibition on Cd-uptake and transport and the enhancement on anti-oxidative enzyme activities, as well as the Lsi1 -related expression on regulation of Si-uptake in rice. A new avenue might become available for overcoming the rampant pollution that threatens the rice production in China.